La Corte Penal Internacional ante un mar abierto. ¿cómo se aplica el estatuto en los conflictos armados internacionales navales? - Sifontes Torres, Efrén Ismael (2021)
In the context of contemporary International Criminal Law, the war crimes that can be committed during an international armed conflicts are currently enshrined in the articles 8.2.a and 8.2.b of the Rome Statute. Therefore, this research starts from a hypothesis that considers these articles as the result of the codification of conducts using instruments of international humanitarian law whose territorial scope is essentially (except for a few counted exceptions) the armed conflicts on land. This assertion opens some questions because one can ask oneself if the Statute applies to international armed conflicts that occurs at sea. The straightforward answer seems to be a plain yes because there are no distinctions of this nature on the Statute. However, one has to consider that the law that applies to both types of armed conflicts can in most cases be different because in an armed conflicts that occurs at sea, the principal target of the belligerent parties are not human beings themselves, but platforms instead. In addition, the international law that applies to armed conflicts at sea has some institutes that cannot find their correlate to those that happen in the mainland. In consequence, the enquiry in this matter is if these institutes are also considered in the Statute´s system and if so, with which scope. These are some of the questions and contradictions that motivates this research. Through the study of the territorial jurisdiction requirements and some conducts contemplated as crimes within jurisdiction of the Court, I aim to bring light to each of these questions, using both the normative system that arises from the Statute and the applicable international humanitarian law to armed conflicts at sea. This last group of norms, will be proved to have a crucial role in the understanding of how the Statute applies to these conflicts, although they are not expressly recognized on it